European Citizens' Attitudes on the Return of Refugees to Their Home Country: Results from a~Survey in 13~EU Member States - Jürgen Gerhards; Clara Dilger (Politische Vierteljahresschrift, 2020)
European law requires member states of the European Union (EU) to accept refugees. It also allows them to return refugees to their countries of origin if the reason for asylum no longer exists. Both the reception and return of refugees has become a~widely debated and controversial issue in many member states of the EU. Based on a~survey conducted in 13~EU member states, we analysed whether citizens support the return of refugees when the cause for their displacement has become obsolete and how differences in attitudes toward the return of refugees can be explained. A~clear majority of Europeans (70%) support the return of refugees. This is also the case for those who believe that their country should accept refugees in the first place. These results mean that existing law—the acceptance of refugees in need and the return when the cause becomes obsolete—is being supported by a~majority of Europeans. However, there are considerable differences in approval rates among the countries. The results of multivariate analysis show that ideational factors—both on the micro and the macro level—influence attitudes toward the return of refugees, whereas structural factors, recurring to economic interest, do not contribute substantially to the explanation of attitudes toward the return. The political implications of these findings are discussed in the last section of the article.
Keywords: 320; Asylum; Refugee policy; Public opinion; Survey research; Europe; Asyl; Flüchtlingspolitik; Öffentliche Meinung; Umfrageforschung; Europa